ANALISIS KEMAMPUAN PENGUASAAN KOSAKATA BAHASA ARAB MELALUI BUKU “BELAJAR CEPAT TATA BAHASA ARAB “ DI UIN SULTHAN TAHA SAIFUDIN JAMBI - Ismail Fahri; Sri Sudiarti (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2023)
The purpose of this research is to find out and uncover, 1) Implementation of the Arabic Learning process in the Arabic language and literature department of UIN Sulthan Thaha Saifuddin Jambi, 2) the steps of teaching Arabic by the Arabic language lecturers through the book Al-Qawaid al-Arabiyah al-Muyassarah